2011
DOI: 10.1186/cc10424
|View full text |Cite
|
Sign up to set email alerts
|

Bench-to-beside review: Acute-on-chronic liver failure - linking the gut, liver and systemic circulation

Abstract: The concept of acute-on-chronic liver failure (ACLF) was introduced recently to describe a subset of patients with chronic liver disease presenting with profound deterioration of liver function and rapidly evolving multi-organ failure. ACLF is frequently accompanied by the development of severe inflammatory response syndrome and has a high mortality. To date, treatment options are limited and exclusively supportive. Over the last few years, some insights have been generated in the pathophysiology of ACLF. A ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 96 publications
(138 reference statements)
1
40
0
Order By: Relevance
“…ies from the East have documented viral hepatitis as the most frequent. Similarly, in Western countries, the most common causes of AI are alcoholic hepatitis, followed by sepsis and upper GI bleeding, while reactivation of hepatitis B virus infection is the most common cause of AI in Asian countries [2,15,16]. Most of our patients exhibited severe liver dysfunction on admission, with high icterus and decreased synthetic and metabolic liver function, and the majority had ascites, encephalopathy, or both.…”
Section: Hbv Hepatitis B Virus Hcv Hepatitis C Virusmentioning
confidence: 93%
“…ies from the East have documented viral hepatitis as the most frequent. Similarly, in Western countries, the most common causes of AI are alcoholic hepatitis, followed by sepsis and upper GI bleeding, while reactivation of hepatitis B virus infection is the most common cause of AI in Asian countries [2,15,16]. Most of our patients exhibited severe liver dysfunction on admission, with high icterus and decreased synthetic and metabolic liver function, and the majority had ascites, encephalopathy, or both.…”
Section: Hbv Hepatitis B Virus Hcv Hepatitis C Virusmentioning
confidence: 93%
“…And lastly, the short-term (3-month) mortality is significantly higher than expected with chronic hepatic decompensation. 11,12 ACLF is frequently accompanied by the development of severe inflammatory response syndrome associated with multi-organ failure leading to high in-hospital mortality despite costly intensive care therapy. 13,12 Basically all organ systems can be affected, particularly circulation, brain, kidneys and liver.…”
Section: Concept Of Acute-on-chronic Liver Failurementioning
confidence: 99%
“…11,12 ACLF is frequently accompanied by the development of severe inflammatory response syndrome associated with multi-organ failure leading to high in-hospital mortality despite costly intensive care therapy. 13,12 Basically all organ systems can be affected, particularly circulation, brain, kidneys and liver. A key role for the interaction of innate immune dysfunction, enhanced bacterial translocation from the gut, and circulatory dysfunction has been proposed.…”
Section: Concept Of Acute-on-chronic Liver Failurementioning
confidence: 99%
“…With disease progression of cirrhosis toward decompensation, the extend of pathological bacterial translocation increases and consequently immune paresis and predisposition to infections [18,46]. Portal hypertension is an important factor triggering the increase of bacterial translocation [18]. However, a large study in humans revealed that severity of liver disease (Child-Pugh Score) rather than the degree of portal hypertension predicted the prevalence of bacterial translocation [48].…”
Section: Infection Related Mortality In Acute-on-chronic Liver Failurementioning
confidence: 97%
“…Inflammatory responses further aggravate the underlying endothelial barrier and GALT dysfunction [47]. With disease progression of cirrhosis toward decompensation, the extend of pathological bacterial translocation increases and consequently immune paresis and predisposition to infections [18,46]. Portal hypertension is an important factor triggering the increase of bacterial translocation [18].…”
Section: Infection Related Mortality In Acute-on-chronic Liver Failurementioning
confidence: 99%